Modelling cell cycle entrainment during cortical brain development - Barrack, Duncan (2010)
Radial glial cells play an important role during embryonic development in mammals. They are not only important for neural production but help to organise the architecture of the neocortex. Glial cells proliferate during the development of the brain in the embryo, before differentiating to produce neurons at a rate which increases towards the end of embryonic brain development. Glial cells communicate via Adenosine tri-phosphate (ATP) mediated calcium waves, which may have the effect of locally synchronising cell cycles, so that clusters of cells proliferate together, shedding cells in uniform sheets. Hence radial glial cells are not only responsible for the production of most neocortical neurons but also contribute to the architecture of the brain. It has been argued that human developmental disorders which are associated with cortical malfunctions such as infantile epilepsies and mental retardation may involve defects in neuronal production and/or architecture and mathematical modelling may shed some light upon these disorders.